# If (a – b) is 13 more than (c + d) and (a + b) is 3 less than (c – d), then (a – c) is:

If (a – b) is 13 more than (c + d) and (a + b) is 3 less than (c – d), then (a – c) is:

## Answer/Solution

5

### Steps/Work

(a – b) – (c + d) = 13 and (c – d) – (a + b) = 3

=> (a – c) – (b + d) = 13 and (c – a) – (b + d) = 3

=> (b + d) = (a – c) – 13 and (b + d) = (c – a) – 3

=> (a – c) – 13 = (c – a) – 3 => 2(a – c) = 10 => (a – c) = 5

ANSWER:E

=> (a – c) – (b + d) = 13 and (c – a) – (b + d) = 3

=> (b + d) = (a – c) – 13 and (b + d) = (c – a) – 3

=> (a – c) – 13 = (c – a) – 3 => 2(a – c) = 10 => (a – c) = 5

ANSWER:E